Prevalence of sunscreen usage and perception about sun exposure and sunscreen—a lower-middle-income country’s perspective - Rukhsar, Shayana; Masood, Sadia; Ghulam , Unzela; Hannan , Eisha (Journal of the Pakistan Medical Association, 2023)
Sunlight is required for vitamin D synthesis but is also responsible for various adverse effects on human skin, including photoaging, sunburn, and skin cancer. To avoid this, regular use of sunscreens is recommended. The aim of the study was to evaluate the knowledge of a subset of our local population about exposure to sun and assess the attitude about the importance of sunscreen usage. This prospective cross-sectional study was conducted at the dermatology outpatient clinic using a predesigned questionnaire filled by the participants. A total of 200 patients were selected, out of which 135 were females and 65 were males. Forty-nine percent of the participants claimed to use sunblock; however, the majority (54%) used it only occasionally. —Continue